Acute HIV infection in a large teaching hospital in western China: Clinical, virological, and molecular epidemiological characteristics. Issue 12 (21st August 2020) - Zhang, Keyi; Wei, Bin; Tang, Zhuoyun; Wei, Yinhao; Zhao, Zhongyi; Li, Dongdong; Tao, Chuanmin
Abstract: Objective: To provide information on clinical, virological, and molecular epidemiological characteristics for early identification, diagnosis, and treatment of acute HIV infection (AHI). Methods: A retrospective study was conducted with patients with AHI from 2012 to 2017 in West China Hospital. Results: A total of 47 patients with AHI were found using a fourth‐generation kit. Thirteen (27.66%) of these patients were negative if tested by third‐generation tests. Median age of patients with AHI was 26 and 91.49% of them were males. Homosexual contact was responsible for 46.81% of AHI transmission. Among the individuals with AHI, 80.85% were outpatients. Common symptoms/signs were fever, headache, rash, cough and sputum, and sore throat. The syphilis coinfection rate was 17.24%. Most of the AHI was distributed in Fiebig stages IV (61.70%) and II (27.66%) with different clinical and virological characteristics. The increasing trend of cut‐off index values was obvious in the course of AHI, helpful for auxiliary diagnosis. The main genetic forms of AHI were CRF07_BC and CRF01_AE, and a rare subtype CRF55_01B in Sichuan province was found. The drug resistance mutation rate was relatively high (17.65%) and five different mutations were identified. Conclusions: Fourth‐generation assays are strongly recommended for screening AHI compared to third‐generation ones. Different clinical and virological characteristics in different Fiebig stages were found. Young individuals and outpatients were the majority of patients with AHI and this deserves special attention. Attention should also be paid to the rare CRF55_01B in Sichuan province and surveillance of HIV resistance ought to be strengthened. Highlights: This study is a systematic research on comprehensive characteristics of AHI in a large teaching hospital and enriched information for early identification, diagnosis and treatment of HIV.